Analisis Tingkat Bahaya Erosi dengan Metode USLE (Universal Soil Losses Equation) di Perkebunan Kelapa Sawit PTPN IV Kebun Berangir Kabupaten Labuhanbatu Utara - Wisnu Wardana Lubis; Yusmaidar Sepriani; Widya Lestari (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2023)
PTPN IV, the Berangir business unit, has some flat-sloping areas and most of them are hilly which are prone to erosion. Erosion needs to be known as early as possible so that land damage due to erosion can be avoided. This study aims to determine the level of erosion hazard that occurs using the USLE (Universal Soil Losses Equation) method at the PTPN IV oil palm plantation business unit Berangir Perkbunan Berangir Village, NA IX-X District, North Labuhanbatu Regency. This research was conducted from March to May 2021, using an exploratory descriptive method through a field survey, followed by using the USLE method to predict erosion. Parameters observed were rain erodibility, soil erodibility, slope length and slope, plants, and soil conservation measures. The results of this study indicate the level of erosion hazard ranges from 11,694-7819,104 tons/ha/year. The highest actual erosion value was found in the sample of 20 Afd V, which was 7819.104 tons/ha/yr with typic paleudults soil type and steep slopes. The lowest actual erosion value is found in sample 3 Afd I, which is 11,694 tons/ha/yr with psammentic paleudults soil type and gentle slope. Keywords: Plantation, Erosion, USLE (Universal Soil Losses Equation)